Teknik Sosiodrama Dalam Layanan Bimbingan Kelompok Untuk Mereduksi Konformitas Teman Sebaya - Wijayanti, Nopi; Asri Widiyanti, Nopi (Universitas Nusantara PGRI Kediri, 2021)
Negative peer conformity has a negative impact on adolescent development. Thisqstudy aims tonanalyze theoeffectiveness ofosociodrama techniques in groupxguidanceoservices to reduce peer conformity in students. Thisbresearch isna quantitativeostudy usingxan experimentalbmethodkwith a quasi experimental design. Theosample inothis studycwas obtainedufrom akquestionnaire about negative peer conformity usingepurposiveqsampling technique, amountingnto 12npeople. Thegresults ofcthis study indicate that based on testing of the data obtained using the Mann-Whitney formula, it shows that the pretest rank = 21.00 and the Postest Rank = 57.00. Furthermore, in the table of the Mann-Whitney U row Statistics, it is known that the value of U 0.0 is obtained by the value of U 0.0 and p-value = 0.004 / 2 = 0.002 <0.05. The conclusion is that there is a difference in the level of peer conformity before and after. Given sociodrama techniques in group guidance services. So the sociodrama technique in group guidance services is effective in reducing peer conformity in class XI students at SMAN 12 Banjarmasin.